Huella Hídrica azul del sector petrolero en Colombia y su relación con otros sectores económicos (2020)
The purpose of this monograph is to study the blue water footprint of the oil sector in the Orinoquía region (3.4 million m3), and in turn, make a comparison of the blue water footprint with respect to other blue water footprints of the different economic sectors in Colombia. For that end, data related to the state of the water resource for the country was collected, which embrances supply, demand and quality to understand the current panorama of the resource. In addition, the issue of real water consumption for the hydrocarbons sector (68 million m3) was deepened to understand the impact that this industry has on the water resource. Finally, the blue water footprint of the hydrocarbons sector was calculated based on the methodology proposed by IDEAM, for which the production data relevant to oil fields month by month and the indicators for such calculation had to be sought.